Behavioral response of Aedes aegypti (Diptera: Culicidae) to essential oils of Cymbopogon nardus (L.) Eucalyptus camaldulensis (Dehnh) and their blend in Y-maze olfactometer - Wangrawa, Dimitri Wendgida; Chandrasegaran, Karthikeyan; Upshur, Forde; Borovsky, Dov; Sharakhov, Igor V.; Vinauger, Clement; Badolo, Athanase; Sanon, Antoine; Lahondère, Chloé (Frontiers in Tropical Diseases, 2024)
BackgroundAedes aegypti vectors several important arboviruses including dengue and yellow fever. This vector mosquito is controlled mainly by using synthetic insecticides and repellents. Overusing these insecticides causes mosquito resistance, harms the environment, and affects human health. This report reevaluates the repellent activities of Cymbopogon nardus, Eucalyptus camaldulensis essential oils (EOs), and their mixtures against laboratory-reared adult Ae. aegypti.MethodsThe chemical composition of C. nardus, E. camaldulensis EOs, and their 1:1 combination was identified by gas chromatography-mass spectrometry (GC-MS). We evaluated the repellent activities of these oils against Ae. aegypti using a Y-maze olfactometer. The preference index (PI) was evaluated and compared with the binary data obtained from the olfactometer assay with samples that did not contain EOs (control) using an Exact Binomial test (α= 0.05)ResultsSeveral monoterpenes and sesquiterpene compounds were found in EOs and their mixture. The EOs of E. camaldulensis and the mixture of the two oils showed a repellent activity of 50%, whereas C. nardus was less active and attracted mosquitoes at 1 ppm.ConclusionWe show that EOs from C. nardus and E. camaldulensis contain compounds that repel Ae. aegypti. Future studies will identify specific compounds with the highest repellent activities and use them to formulate in the future a potent repellent against Ae. aegypti for human protection.